Science and technology in the age of Hawthorne, Melville, Twain, and James thinking and writing electricity - Halliday, Sam (American literature readings in the 21st century., 2007)
This innovative book reveals the full extent of electricity's significance in nineteenth- and early-twentieth-century culture. Ranging across a vast array of materials, Sam Halliday shows how electricity functioned as both a means of representing other things--from love and solidarity to embodiment and temporality--and as an object of representation in its own right. As well as Hawthorne, Melville, Twain and James, the book considers other major American writers such as Whitman, Margaret Fuller and Henry Adams; English writers such as Hardy and Kipling; and a galaxy of scientists and social commentators, including mesmerists, physicians, conspiracy theorists, psychologists and theologians.